2008
DOI: 10.1111/j.1748-5967.2008.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Body melanization and its adaptive role in thermoregulation and tolerance against desiccating conditions in drosophilids

Abstract: Melanism seems to have evolved independently through diverse mechanisms in various taxa and different ecological factors could be responsible for selective responses. Increased body melanization at higher altitudes as well as latitudes is generally considered to be adaptive for thermoregulation. Physiological traits such as body melanization and desiccation resistance have been investigated independently in diverse insect taxa at three levels: within populations, between populations and among species. A substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 63 publications
1
90
1
Order By: Relevance
“…Laboratory selected dark and light strains in D. melanogaster might differ significantly in their desiccation resistance level but this aspect has not been analyzed so far. However, a positive correlation between body melanisation and desiccation resistance is evident from the analysis of yellow body color mutant strain of D. melanogaster (Kalmus 1941); and on the basis of assorted darker and lighter flies in populations of different Drosophila species (Rajpurohit et al 2008). In D. melanogaster, we found significant differences in desiccation resistance levels between assorted dark and light flies from a given population (Parkash et al 2008a, d).…”
Section: Discussionmentioning
confidence: 97%
“…Laboratory selected dark and light strains in D. melanogaster might differ significantly in their desiccation resistance level but this aspect has not been analyzed so far. However, a positive correlation between body melanisation and desiccation resistance is evident from the analysis of yellow body color mutant strain of D. melanogaster (Kalmus 1941); and on the basis of assorted darker and lighter flies in populations of different Drosophila species (Rajpurohit et al 2008). In D. melanogaster, we found significant differences in desiccation resistance levels between assorted dark and light flies from a given population (Parkash et al 2008a, d).…”
Section: Discussionmentioning
confidence: 97%
“…Such a mismatch between field and laboratory selection may be due to selection acting on some other associated trait that may impact resistance to starvation and desiccation in different ways. There is ample empirical support for the thermal melanism hypothesis (Watt, 1969;David et al, 1985;David et al, 1990;Jong et al, 1996;Majerus, 1998;Rajpurohit et al, 2008). Several studies have demonstrated a direct influence of melanisation on body temperature by increasing solar absorption under cool conditions (Jong et al, 1996;Ottenheim et al, 1999;Ellers and Boggs, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In no Drosophila species except where pigmentation is sex-specific is the ecological force that selected for the dark phenotype known. Dark pigmentation of some Drosophila species tends to associate with higher altitudes, where the coloration may help the flies regulate temperature or prevent desiccation through the control of cuticular water loss (Gibert et al, 1998;Brisson et al, 2005;Pool and Aquadro, 2007;Rajpurohit et al, 2008). However, based on climate data, the geographic range of D. tenebrosa is not generally colder or drier compared with the boreal forests of the northern North America, where D. suboccidentalis and several other lightly colored and closely related quinaria group species occur.…”
Section: Discussionmentioning
confidence: 99%